A Network-Based Approach to Investigate the Neuroprotective Effects and Mechanisms of Action of Huangqi-Chuanxiong and Sanleng-Ezhu Herb Pairs in the Treatment of Cerebral Ischemic Stroke - Zhao, Lin; Ding, Li Dong; Xia, Zi Hao; Sheng, Peng; Shen, Meng Meng; Cai, Zhong Ming; Yan, Bing Chun (Frontiers in Pharmacology, 2022)
Objective: We aimed to investigate the effect and mechanisms of action of two drug pairs (Huangqi-Chuanxiong and Sanleng-Ezhu Herb (HCSE)) on the treatment of ischemic stroke. Materials and methods: We mined the current literature related to ischemic stroke and formulated a new formulation of Chinese herbs. Then, we identified the main candidate target genes of the new formulation by network pharmacology. Next, we performed enrichment analysis of the target genes to identify the potential mechanism of action of the new formulation in the treatment of ischemic stroke. Next, we experimentally validated the mechanism of action of the new formulation against ischemic stroke. Infarct volume and neurological deficits were evaluated by 2,3,5-triphenyltetrazolium (TTC) staining and Longa’s score, respectively. The predicted pathways of signal-related proteins were detected by western blotting. Results: We mined the current literature and identified a new formulation of Chinese herbs for the treatment of ischemic stroke. The formulation included Huangqi, Chuanxiong, Sanleng and Ezhu. Next, we used network pharmacological analysis to identify 23 active compounds and 327 target genes for the new formulation. The key target genes were MAPK3, MAPK1, HSP90AA1, STAT3, PIK3R1, PIK3CA and AKT1. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed significant enrichment of the PI3K/AKT and MAPK/ERK signaling pathways. By performing experiments, we found that the new formulation reduced the infarct volume of middle cerebral artery occlusion (MCAO) induced mice and activated the PI3K/AKT and MAPK/ERK signaling pathways. These findings confirmed that the new formulation has a significant protective effect against ischemic stroke injury by activating the PI3K/AKT and MAPK/ERK signaling pathways. Conclusion: We identified a new treatment formulation for ischemic stroke by data mining and network pharmacological target prediction. The beneficial effects of the new formulation act by regulating multiple target genes and pathways. The mechanism of action of the new formulation may be related to the AKT and ERK signaling pathways. Our findings provide a theoretical basis for the effects of the new formulation on ischemic stroke injury.